The Study of Spoken Word's Effect as a Technique to Increase Student's Confidence in Public Speaking of SMK Nurul Huda Sukaraja - Ahmad Fauzi Syah; Setyaningsih, Eka; Farhan Fahrudin, Aris; Nursyahid, Aldi; Muklas, Muhamad (ENJEL: English Journal of Education and Literature, 2022)
This study aims to show a new technique that has been discovered and implemented by the author to increase confidence in public speaking for students at Nurul Huda Vocational High School. The technique is Spoken Word Learning. In the implementation process which aims to get the best results, this study uses quantitative methods. The design involves quasi-experimental research. There are 124 populations consisting of students of class XI SMK Nurul Huda, and the sample is 55 students who are divided into two groups, namely experimental organization and control organization. The results of this study are divided into two, namely the results for the experimental organization and the control organization.